A genre-based analysis of tourism homepages of Thailand / Daruni Krairak - Daruni, Krairak (2012)
The research is a genre-based analysis of tourism homepages of Thailand. The study mainly aims to explore the move structures and linguistic features of the tourism homepages. Data were collected from 30 Thai-tourism websites using the framework of move analysis developed by Bhatia (1993) and Askehave and Nielson (2005). Only the homepage of each website was used for the analysis. In addition, a computerized concordancing programme named “Concapp Concordance Browser and Editor” by Greaves (1993-2008) was used to identify and analyze prominent linguistic features of the moves. The results reveal that the prototypical move structure consists of 4 moves: 1) Identifying the Attraction; 2) Establishing Credentials; 3) Introducing the Offers; 4) Soliciting Response. Each move comprises various steps which help to accomplish the communicative purpose of the moves. The personal pronoun „you‟, the modal verb „can‟, imperatives and adjectival pre-modifiers are prominently used in the texts. In addition, the persuasive communicative purpose tends to be the main purpose of the texts. The moves and linguistic features found in the investigated tourism homepages tend to contribute to the overall persuasive communicative purpose of the texts. The output from the analysis could be used as a model for web writers of tourism homepages. In addition, the findings can be used as guidelines for lecturers in this genre in designing of syllabi, teaching materials and teaching strategies for English tourism courses. This would contribute to improvements in the writing of the tourism homepages particularly in Thailand and other countries where English is not the first language, thus serving as a way to improve communications in marketing the tourism industry